Christmas in the movies : 30 classics to celebrate the season - Arnold, Jeremy (Turner Classic Movies British film guide, 2018)
"Turner Classic Movies presents a bucket list of the best and most beloved holiday films of all time, complete with spirited commentary, behind-the-scenes stories, and photos spanning eight decades of Christmastime favorites. Nothing brings the spirit of the season into our hearts quite like a great holiday movie. "Christmas films" come in many shapes and sizes and exist across many genres. Some, like It's a Wonderful Life and A Christmas Story, are perennials, while others, such as Die Hard, have only gradually become yuletide favorites. But they all have one thing in common: they use themes evoked by the holiday period - nostalgia, joy, togetherness, dysfunction, commercialism, or cynicism - as a force in their storytelling. Turner Classic Movies: Christmas in the Movies showcases the very best among this uniquely spirited strain of cinema. Each film is profiled on what makes it a "Christmas movie," along with behind-the-scenes stories of its production, reception, and legacy. Complemented by a trove of color and black-and-white photos, Turner Classic Movies: Christmas in the Movies is a glorious salute to a collection of the most treasured films of all time. Among the 30 films included: The Shop Around the Corner, Holiday Inn, Meet Me in St. Louis, It's a Wonderful Life, Miracle on 34th Street, White Christmas, A Christmas Story, National Lampoon's Christmas Vacation, Home Alone, Little Women, and The Nightmare Before Christmas."--provided by publisher.